Revenue Allocation and the Challenge of Federalism in Nigeria - Godwin Orakpowenri Orovwiroro; Agbajeogu Evelyn Nwa-Amaka Ochi; Oruta Lawrence Igwe (International Journal of Sustainable Applied Sciences, 2023)
This paper is focused on the federal government revue allocation and the challenges of allocations   The method of data analysis adopted  is the qualitative descriptive method of investigation.  The qualitative research method deals with variables that are not easily manipulated to empirical measurement or verification. The poor structural layout of the Nigerian federalism is rooted in our colonial history, our colonial history affects the structure of the federal system we are operating the paper made the following recommendation amongst others, the Nigeria state should be restructured to reflect fiscal federalism in its character and composition.